Cellular immune responses of older adults to four influenza vaccines: Results of a randomized, controlled comparison - Arun Kumar; Janet E. McElhaney; Lisa Walrond; Terry D. Cyr; Shahzma Merani; Tobias R. Kollmann; Scott A. Halperin; David W. Scheifele (Taylor & Francis Group, 2017)
Cellular immunity is important for protection against the serious complications of influenza in older adults. As it is unclear if newer influenza vaccines elicit greater cellular responses than standard vaccines, we compared responses to 2 standard and 2 newer licensed trivalent inactivated vaccines (TIVs) in a randomized trial in older adults. Non-frail adults ≥ 65 y old were randomly assigned to receive standard subunit, MF59-adjuvanted subunit, standard split-virus or intradermal split-virus TIV. Peripheral blood mononuclear cells (PBMC) harvested pre- and 3-weeks post-vaccination were stimulated with live A/H3N2 virus. PBMC supernatants were tested for interleukin 10 (IL-10) and interferon gamma (IFN-γ), and lysates for granzyme B (GrB). Flow cytometry identified CD4+ and CD8+ T- cells expressing intracellular IL-2, IL-10, IFN-γ, GrB, or perforin. Differences following immunization were assessed for paired subject samples and among vaccines. 120 seniors participated, 29-31 per group, which were well matched demographically. Virus-stimulated PBMCs were GrB-rich before and after vaccination, with minimal increases evident. Immunization did not increase secretion of IFN-γ or IL-10. However, cytolytic effector T-cells (CD8+GrB+perforin+) increased significantly in percentage post-vaccination in all groups, to similar mean values across groups. CD4+GrB+perforin+ T-cells also increased significantly after each vaccine, to similar mean values among vaccines. Vaccination did not increase the low baseline percentages of CD4+ or CD8+ T-cells expressing IFN-γ, IL-2 or IL-10 . In conclusion, participants had pre-existing cellular immunity to H3N2 virus. All 4 vaccines boosted cellular responses to a similar but limited extent, particularly cytolytic effector CD8+ T-cells associated with clinical protection against influenza.